(untitled) (Damascus University Journal for engineering sciences, 2021)
This research aims to explain a working mechanism, encryption algorithm, and weaknesses of Wired Equivalent Privacy (WEP) Wi-Fi security protocol ,and attacks against it. We will focus on korek’s key recovery attacks, which are seventeen attacks published on the web as a source code by person called Korek . but, because Korek was not engaged in the details and didn’t explain the mechanism of action of this attacks ,we try to study these attacks in depth and explain the principles of its work , in addition we try to implement these attacks and evaluate its work and make comparison between it. This research also aims to highlight the vulnerabilities of this protocol and the ease of breaking the protection, aiming to more reliable and secure protection protocols. A recent study showed that about 40% of wireless networks are using this protocol as a protection method until today.